Modern Language Review: tomo 48 (1953), tomo 49 (1954), tomo 50 (1955). - F. G. (Nueva Revista de Filología Hispánica, 1971)
Se reseñó: Modern Language Review: tomo 48 (1953), tomo 49 (1954), tomo 50 (1955).